Unusual molecular architecture of the machupo virus attachment glycoprotein - Bowden, T; Crispin, M; Graham, S; Harvey, D; Grimes, J; Jones, E; Stuart, D (American Society for Microbiology, 2009)
New World arenaviruses, which cause severe hemorrhagic fever, rely upon their envelope glycoproteins for attachment and fusion into their host cell. Here we present the crystal structure of the Machupo virus GP1 attachment glycoprotein, which is responsible for high-affinity binding at the cell surface to the transferrin receptor. This first structure of an arenavirus glycoprotein shows that GP1 consists of a novel alpha/beta fold. This provides a blueprint of the New World arenavirus attachment glycoproteins and reveals a new architecture of viral attachment, using a protein fold of unknown origins.